PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DINAS CIPTA KARYA, TATA RUANG DAN KEBERSIHAN KABUPATEN KUBU RAYA (STUDI KASUS PADA DINAS CIPTA KARYA, TATA RUANG DAN KEBERSIHAN KABUPATEN KUBU RAYA) - B31111101, Bino Yanuar Afdillah (Jurnal Manajemen Update, 2016)
This study aimed to determine and provide empirical evidence about whether the variable quality of care that is financial compensation, non-financial compensation, work motivation on the performance of the employee Dinas Cipta Karya, Tata Ruang dan Kebersihan Kabupaten Kubu Raya. This study used multiple linear regression analysis using SPSS 16. The population used was employee Dinas Cipta Karya, Tata Ruang dan Kebersihan Kabupaten Kubu Raya. The samples used were 66 votes against employees Dinas Cipta Karya, Tata Ruang dan Kebersihan Kabupaten Kubu Raya by purposive sampling method. The results of multiple regression analysis that has been done shows that, Y = 0.474 X1 + 0,368 X2 + 0,156 X3. The independent variables that most influence on the dependent variable is the variable of financial compensation (0.474), followed by variable of non-financial compensation (0,368), then the variable work motivation (0,156). T test results prove that all independent variables (financial compensation, non-financial compensation, work motivation) has a positive effect on the dependent variable, namely work performance. The coefficient of determination (R Square) obtained at 0,897 . This means that 89.7% work performance is affected by the variable compensation of financial, non financial compensation, work motivation, and the remaining 10.3% is influenced by other variable. Keyword : Financial Compensation, Non Financial Compensation, Work Motivation and Employee Performance.